Institutional adaptation of public administration to climate change: strengthening environmental resilience through adaptive governance - Raden Deni Atmiral; Ahmad Fauzan; Mardiansyah Manurung (Lentera Negeri, 2026)
Climate change poses significant challenges to environmental sustainability and governance, particularly in developing countries such as Indonesia, where increasing frequencies of natural disasters, ecosystem degradation, and food security risks require adaptive policy responses. This study analyzes the adaptation of public administration policies to climate change and their role in strengthening environmental resilience in Indonesia. Using a qualitative research design, the study examines 15 national policy documents related to climate change adaptation, disaster risk reduction, environmental management, and sustainable development issued between 2014 and 2024. The analysis employs an Adaptive Governance Framework combined with qualitative policy content analysis to evaluate the extent to which environmental resilience principles are integrated into public administration policies. To ensure analytical rigor, policy documents were selected based on relevance, legal authority, and implementation scope, while coding reliability was enhanced through systematic category development and cross-document comparison.The findings indicate that environmental resilience has been formally incorporated into most national climate-related policies; however, policy implementation remains constrained by institutional fragmentation, limited intergovernmental coordination, and uneven resource allocation across regions. The analysis further reveals that policy integration is strongest in disaster risk reduction and environmental protection sectors but remains weak in cross-sectoral administrative coordination and local-level implementation mechanisms. These findings suggest that strengthening adaptive governance capacities, improving policy coherence, and enhancing collaboration among central government, local authorities, and non-state actors are critical for achieving long-term environmental resilience. The study concludes that Indonesian public administration requires a more integrated and adaptive governance approach to effectively address climate change challenges and support sustainable development objectives.